2017
DOI: 10.1021/jacs.7b03131
|View full text |Cite
|
Sign up to set email alerts
|

Derisking the Cu-Mediated 18F-Fluorination of Heterocyclic Positron Emission Tomography Radioligands

Abstract: Molecules labeled with fluorine-18 (F) are used in positron emission tomography to visualize, characterize and measure biological processes in the body. Despite recent advances in the incorporation of F onto arenes, the development of general and efficient approaches to label radioligands necessary for drug discovery programs remains a significant task. This full account describes a derisking approach toward the radiosynthesis of heterocyclic positron emission tomography (PET) radioligands using the copper-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
168
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(175 citation statements)
references
References 52 publications
4
168
0
3
Order By: Relevance
“…To challenge the chemistry further, the optimized [ 18 F]KF dissolution/order of addition with KOTf/K 2 CO 3 eluent was applied to the synthesis of [ 18 F]‐( ± )‐IPMICF17 ( 2‐F ), a PET radiotracer for TrkB/C that is currently being developed by the Schirrmacher and Scott groups (Scheme ) . We expected this molecule to be amenable to such labeling because it has been previously demonstrated that the 6‐(pyrrolidin‐1‐yl)imidazo[1,2‐b]pyridazine core does not inhibit Cu‐mediated fluorination reactions . Synthesis from the ( ± )‐IPMICF17 Bpin precursor ( 2‐Bpin ) was carried out both manually and in an automated format, with predissolution of [ 18 F]KF performed with a precursor/DMF solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To challenge the chemistry further, the optimized [ 18 F]KF dissolution/order of addition with KOTf/K 2 CO 3 eluent was applied to the synthesis of [ 18 F]‐( ± )‐IPMICF17 ( 2‐F ), a PET radiotracer for TrkB/C that is currently being developed by the Schirrmacher and Scott groups (Scheme ) . We expected this molecule to be amenable to such labeling because it has been previously demonstrated that the 6‐(pyrrolidin‐1‐yl)imidazo[1,2‐b]pyridazine core does not inhibit Cu‐mediated fluorination reactions . Synthesis from the ( ± )‐IPMICF17 Bpin precursor ( 2‐Bpin ) was carried out both manually and in an automated format, with predissolution of [ 18 F]KF performed with a precursor/DMF solution.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction utilizes a small quantity of aryl boron precursor (4 μmol), which facilitates adaption of the chemistry for automation and purification by semipreparative HPLC and solid phase extraction. Subsequently, we and others have also optimized this chemistry further, including exploring substrate scope, functional group tolerance, and developing alternate labeling conditions . However, most of these reports have conducted most of the chemistry in a “manual” format, wherein a stock solution of nucleophilic [ 18 F]fluoride is divided into aliquots and used in multiple reactions carried out in sealed vials or in a synthesis module.…”
Section: Introductionmentioning
confidence: 99%
“…Ar eaction at reflux conditions improved the yield of 3i to 81 % (entry 19). An increasei na mount of IBX (entries [20][21][22] showedb est resultsw ith 2.0 equiv IBX providing 3i in 94 % yield in a3hr eaction ( entry 20). Theh igher loading of IBX over 2.0 equiv was not beneficial.…”
Section: Resultsmentioning
confidence: 99%
“…13 3-(4-Fluorophenyl)propan-1-ol (22 d). [22] Colourless oil (1.357 g, 44 %). 3-(3-Bromophenyl)propan-1-ol (22 e).…”
Section: Methodsmentioning
confidence: 99%
“…[150,151] Besides aryl-BPin and the copper triflate pyridine system, Sanford, Scott, and co-workers independently developed aC u-mediated 18 F-fluorination from aryl boronic acid precursors (Scheme 26 B). Ther eaction with aryl-BPin precursors was performed in the presence of Cu(OTf) 2 Py 4 and O 2 ,t he latter of which was necessary and beneficial for 18 F-incorporation.…”
Section: Reviewsmentioning
confidence: 99%